Statistical Analysis Of Solid Waste Generated In Selected Palm Oil Mill In Malaysia. - Ngu, Chard Chard; Alkarkhi, Abbas F.M.; Ahmad, Anees; N.A, Nik Norulaini; Abdul Kadir, Mohd Omar (2009)
Similar types of industry sometimes have different solid waste management. In this study, Discriminant Analysis (DA) and Principal Components Analysis (PCA) were applied to analyze the solid waste generation from the perspective of the amount of solid wastes generated such as empty fruit bunches (EFB), potash ash, fibre, and shell from 5 different oil palm mills industry.